Kim - Rudyard Kipling (North Books, 1901)
He sat, in defiance of municipal orders, astride the gun Zam-Zammah on her brick platform opposite the old Ajaib-Gher-the Wonder House, as the natives call the Lahore Museum.
Métadonnées bibliographiques et couvertures référencées via Open Library / Internet Archive. Vérifier les droits de couverture selon usage final.
Keywords: Inde; voyage; Kipling; classique